Challenges faced by health professionals regarding sex education in adolescence: a supplementary inquiry (Research, Society and Development, 2023)
Sex education is a key issue in the prevention and treatment of sexually transmitted infections (STIs) and AIDS. The current study aimed to understand the importance of adolescents' knowledge about sexuality for individual and joint protection. The current study refers to an Integrative Review, on the problems faced by health professionals regarding sexual education in adolescence. For the realization, the methodology of integrative literature review was used in an integrative approach, adhering as criteria to secondary sources on the subject such as Latin American and Caribbean Literature in Health Sciences (LILACS), Virtual Health Library Brazil (BVS), Scientific Electronic Library Online (SCIELO), Nursing Database (BDENF). This study supports the importance of demonstrating how health professionals should break the taboo when talking about sexuality in adolescence. The lack of family openness to talk about sexuality within spaces where the teenager is safe and protected suggests that the teenager seeks information that prepares him to start a sexual life early and in unpleasant places. The study made it possible to understand that the family can be the main protagonist of their children's sexual education, thus bringing information that teaches how to protect and take care of their own health, avoiding future problems and frustrations.